Rediscovery of the Neotropical orchid Porroglossum parsonsii and recommendations for its conservation - Edicson Parra-Sanchez; Juan Sebastián Moreno; Sebastián Vieira-Uribe; Luis Baquero; David P. Edwards (Oryx)
Understanding the distribution and habitat requirements of species is crucial for designing conservation actions, yet this information is not available for many plant species. We report the first confirmed wild populations of Porroglossum parsonsii, which, because of its horticultural value, is commercialized in national and international markets, from where it was first described to science. Our large-scale survey of 341 10 × 30 m plots spanning Andean forests, paramo habitats and pasturelands in Colombia suggests that P. parsonsii has a restricted geographical distribution in Andean forests with high forest cover (71.4–86.2%), where it occurs in low numbers (5–17 individuals per plot). Because of its market value (USD 18–20 per plant) there is a risk the species could be collected illegally, and therefore the habitat of the species in the Santuario de Fauna y Flora de Iguaque requires appropriate conservation.